Synthesis and characterization of the bulk YBCO-target of superconducting material. (2021) - Hasan, N.; Hafeath, H.; Ahmed, A.
Abstract: Superconducting devices have emerged as promising candidates, due to their outstanding sensitivity, such as wideband and high frequency operation, and Josephson tunnelling junction detectors with high sensitivity which have been developed and applied to THz imaging. This paper presents the details of synthesizing the d-wave superconductor. We applied a standard method of solution-gel combustion to form the high-temperature yttrium barium copper oxide (YBCO) of superconductor materials. To realize bulk superconductor materials, it was used the calcination temperature of 850 °C, and the sintering temperature about 950 °C for 5 h. For characterizing YBCO, we could be realized the critical transition temperature ( Tc ) of about 93 K and conventional R-T dependencies. The formation of the characterizations structural showed that YBCO samples have an orthorhombic crystal structure. As well as the morphology and structure samples tested according to characterize the X-ray diffraction (XRD) analysis data and SEM (scanning electron microscopy).